Effect of carotid artery stenosis on cortical microinfarcts, white matter integrity, and brain volume: An interhemispheric comparison within the population-based Rotterdam Study - Frank J. Wolters; Meike W. Vernooij; Gennady V. Roshchupkin; M․Arfan Ikram; Maryam Kavousi; Peter J. Koudstaal; Aad van der Lugt; Daniel Bos (Cerebral Circulation - Cognition and Behavior, 2025)
Background: Carotid artery stenosis could contribute to gradual loss of brain function through chronic hypoxia and ischemia. Methods: We included consecutive participants of the population-based Rotterdam Study with unilateral ≥50 % stenosis at the carotid artery bifurcation on time-of-flight carotid MR angiography, and compared between hemispheres the presence of ischemic lesions, tissue volumes, and white matter integrity on structural brain MRI. Results: Among 50 participants (mean age 76 years, 50 % women), flow was lower in the affected carotid artery than on the unaffected side (160mL/min versus 202mL/min; flow reduction [95 %CI] per 1 % increase in stenosis: 1.7 mL/min [1.0–2.5]). Twelve individuals had radiographic evidence of cortical infarction, of whom 8 had cortical microinfarcts, all on the side of the stenosis (P = 0.001). Downstream of the stenotic artery, parenchymal volume was lower than in the contralateral hemisphere (mean difference: -2.7 mL [-4.9;-0.4]), similar for grey and white matter. Differences were most profound in the frontoparietal lobes, and increased with severity of stenosis to roughly 5 mL in individuals with ≥70 % stenosis. White matter hyperintensity volume and microstructural integrity did not differ between hemispheres. Conclusions: Carotid artery stenosis is associated with downstream presence of cortical microinfarcts as well as lower parenchymal tissue volume.